The Chinese Revolution. - World Book, Inc. (Chicago World Book, 2011)
"A history of the Communist revolution in China, based on primary source documents and other historical artifacts. Features include period art works and photographs; excerpts from literary works, letters, speeches, broadcasts, and diaries; summary boxes; a timeline; maps; and a list of additional resources"--Provided by publisher.
Winds of change -- China divided -- Conflict with Japan -- China in World War II -- Showdown -- Founding the People's Republic -- The new government -- China expands -- Early reforms -- The Korean War -- Taiwan -- Dealing with dissent -- The great leap forward -- A great leap backward -- Troubles in Tibet -- China begins to recover -- The Soviet Union break -- The Cultural Revolution -- Red Guard terror -- Mao triumphant -- Censorship -- Religion -- Women and family -- Population, health, and education -- China : a nuclear power -- China joins the United Nations -- U.S. President Nixon visits China -- End of the revolution?
Includes bibliographical references and index.
Keywords: Revolutions -- China -- History -- 20th century -- Juvenile literature; Revolutions -- China -- History -- 20th century -- Sources -- Juvenile literature; China -- History -- 20th century -- Juvenile literature; China -- Politics and government -- 1949-1976.; China -- History -- 20th century -- Sources -- Juvenile literature